THE EFFECTIVENESS OF GROUP GUIDANCE USING BIBLIOTHERAPY TECHNIQUES TO IMPROVE PSYCHOLOGICAL WELL-BEING IN 11TH GRADE STUDENTS AT SMA BATIK 1 SURAKARTA - Khoirul Nasywa, Tsaniya (Jurnal Profesi Keguruan, 2024)
This study aimed to assess the effectiveness of group guidance using bibliotherapy techniques to enhance the psychological well-being of 11th-grade students at SMA Batik 1 Surakarta for the 2023/2024 academic year.  The research employed a Quasi-Experimental design with a Nonequivalent Control Group Design.  The study was conducted over three sessions. The subjects were 11th-grade students at SMA Batik 1 Surakarta during the 2023/2024 school year, comprising 16 students divided into groups with 4 students each classified as having low and moderate psychological well-being scores.  Data collection used a psychological well-being scale adapted from Carol D.  Ryff Data analysis was performed using the Mann-Whitney test with SPSS version 26. The analysis revealed that the average pretest score was 225.25, while the average posttest score was 236.38.  Hypothesis testing with the Mann-Whitney test, due to the non-normal distribution of data, yielded a result of 1.000, indicating that the Asymp.Sig (2-tailed) value was greater than 0.05. Consequently, the alternative hypothesis (Ha) was rejected, suggesting no significant difference in psychological well-being scores between the two groups post-treatment. The summary of pretest and posttest data for the experimental group showed an increase of 89 points after the treatment.  However, the control group also exhibited an increase of 164 points, indicating a larger improvement compared to the experimental group.  Based on these findings, it was concluded that the bibliotherapy technique in group guidance was not effective in this study. Recommendations for using bibliotherapy in group guidance include: enhancing group dynamics, using bibliotherapy as an additional treatment, incorporating follow-up activities, selecting appropriate reading materials, considering participants' ability to project the underlying themes of the readings, and increasing the number of service sessions